A Mind Mapping : A Strategy to Enhance Students’ English Grammatical Structure - Furqon Edi Wibowo (Al-Lisan: Jurnal Bahasa, 2020)
The goal of this review was to study about the implementation of Mind Mapping in teaching grammar in the second semester of students of the Department of English Education at IAIN Surakarta. Observation and documentation were the instruments for collecting the data. These instruments were used to collect data on the Mind Mapping process in grammar teaching, problems and solutions. The data analysis technique started with data reduction, data display and verification. First, the findings revealed that the implementation of Mind Mapping in teaching grammar was only used to provide an overview of the material. It was developed by elaborating, questioning, and responding techniques or methods for transferring the material. Mind Mapping made the students active in giving feedback and become a measure in assessing how far the students understood the material during the teaching-learning process, the students were very eager to analyze the material using Mind Mapping. It could be seen from their direct reactions during the teaching-learning process and observed the work of the student in the classroom. Second, there are some advantages to using mind mapping in grammar teaching. They were; (1) giving students an overview of the concept of grammar material; (2) making grammar easier to understand; and (3) helping students to easily memorize the concept of English grammatical structure.